Urban Governance and Tolerance: The Regulation of Suspect Spaces and the Burden of Surveillance in Post–World War I Asheville, North Carolina. (September 2017) - Epstein, Seth
This article reconsiders the relevance of tolerance to urban history in the Southern United States. It examines the surveillance of commercial and residential spaces considered morally suspect by white authorities in post–World War I Asheville, North Carolina. Policing practices involved objects of suspicion in the management of order within pawnshops, dance halls, and African American neighborhoods. The regulation of such suspect spaces distributed the responsibility for surveillance to many actors. Pawnbrokers, dance hall operators, and prominent African Americans all were enlisted and enlisted themselves in policing networks. Participants' involvement in such efforts at times facilitated their claims to self-regulation. These networks, however, did not remove white authorities' suspicions from either the spaces or the individuals who surveilled them. Instead, the arrangements scrutinized here supported those suspicions. Examining the contradictions of these arrangements demonstrates how tolerance informed urban governance within the context of white supremacy.